2021
DOI: 10.3390/biom11111645
|View full text |Cite
|
Sign up to set email alerts
|

Update on Thiamine Triphosphorylated Derivatives and Metabolizing Enzymatic Complexes

Abstract: While the cellular functions of the coenzyme thiamine (vitamin B1) diphosphate (ThDP) are well characterized, the triphosphorylated thiamine derivatives, thiamine triphosphate (ThTP) and adenosine thiamine triphosphate (AThTP), still represent an intriguing mystery. They are present, generally in small amounts, in nearly all organisms, bacteria, fungi, plants, and animals. The synthesis of ThTP seems to require ATP synthase by a mechanism similar to ATP synthesis. In E. coli, ThTP is synthesized during amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 93 publications
(199 reference statements)
0
10
0
1
Order By: Relevance
“…Gangolf et al (2010) reported that TTP is found mainly in brain mitochondria. TTP could thus be pivotal in thiamine deficiency neurotoxicity, but this has not been investigated (see for example Bettendorff, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Gangolf et al (2010) reported that TTP is found mainly in brain mitochondria. TTP could thus be pivotal in thiamine deficiency neurotoxicity, but this has not been investigated (see for example Bettendorff, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The thiamine unit can carry between one and three phosphate moieties, thiamine monophosphate (TMP), thiamine diphosphate (TDP) or thiamine triphosphate (TTP), respectively, which can in turn be adenosylated. However, only adenosine TDP (ATDP) and adenosine TTP (ATTP) have been reported (Bettendorff, 2021).…”
Section: The Vitamin B 1 Family Vitamin B 1 Metabolism In Plants and ...mentioning
confidence: 99%
“…Beyond the coenzyme role in energy metabolism, additional roles for B 1 vitamers have been proposed. In the nervous system of animals, TTP has been implicated in chloride channel regulation, membrane excitability, nerve conduction and neurotransmitter release (Bettendorff, 2021). Furthermore, TTP was also described to phosphorylate rapsyn (a membrane protein that binds acetylcholine receptors); however, the physiological significance of this process remains unknown (Nghiem et al., 2000).…”
Section: The Vitamin B1 Familymentioning
confidence: 99%
“…Thiamin ( 1 ), also known as vitamin B 1 , is an essential cofactor utilized by all domains of life. , The pyrophosphorylated form of thiamin is required for the activity of several enzymes involved in the metabolism of carbohydrates and amino acids, including transketolase in the pentose phosphate pathway, α-ketoglutarate dehydrogenase in the citric acid cycle, and pyruvate dehydrogenasethe critical enzyme connecting glycolysis to the citric acid cycle . Several non-cofactor functions for thiamin have also been reported. …”
Section: Introductionmentioning
confidence: 99%